Sorafenib suppresses growth and survival of hepatoma cells by accelerating degradation of enhancer of zeste homolog 2 - Wang, Shanshan (Cancer Sci, 2013)
Enhancer of zeste homolog 2 (EZH2) is a mammalian histone methyltransferase that contributes to the epigenetic silencing of target genes that regulate cancer cell growth and survival. It is overexpressed in hepatocellular carcinoma (HCC) with a clinical significance that remains obscure. Sorafenib, a multikinase inhibitor, has been used as a first‐line therapeutic drug and shown clinical efficiency for advanced‐stage HCC patients. In the present study, we found that sorafenib lowered the protein level of EZH2 through accelerating proteasome‐mediated EZH2 degradation in hepatoma cells. Overexpression of EZH2 reversed sorafenib‐induced cell growth arrest, cell cycle arrest, and cell apoptosis dependent on histone methyltransferase activity in hepatoma cells. More importantly, shRNA‐mediated EZH2 knockdown or EZH2 inhibition with 3‐deazaneplanocin A treatment promoted sorafenib‐induced hepatoma cell growth arrest and apoptosis. Sorafenib altered the hepatoma epigenome by reducing EZH2 and H3K27 trimethylation. These results revealed a novel therapeutic mechanism underlying sorafenib treatment in suppressing hepatoma growth and survival by accelerating EZH2 degradation. Genetic deletion or pharmacological ablation of EZH2 made hepatoma cells more sensitive to sorafenib, which helps provide a strong framework for exploring innovative combined therapies for advanced‐stage HCC patients.